2022
DOI: 10.52131/pjhss.2022.1001.0189
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic Personality, Social Media and Mental Health in Early Adulthood

Abstract: The purpose of this study was to examine the relationship between social media, narcissism, and the mental health of young adults. It was hypothesized that there is likely to be a relationship between narcissism, social media usage, and mental health in early adulthood. A correlation research design was used to collect data (online) from (N= 160) university students (male =31; female=129) with the age range of 18-25 years (M=19.58, SD=5.27). The sample was recruited by using a convenient sampling technique fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The result showed that there was a positive relation between socialmedia usage and psychological well-being and a negative relation between narcissism and social media usage. The study also revealed no gender difference in social media usage and mental well-being 29 .…”
Section: Discussionmentioning
confidence: 66%
“…The result showed that there was a positive relation between socialmedia usage and psychological well-being and a negative relation between narcissism and social media usage. The study also revealed no gender difference in social media usage and mental well-being 29 .…”
Section: Discussionmentioning
confidence: 66%
“…In this complex digital age, digital literacy and the ability to evaluate the information found on social media have become essential skills. (Batool et al, 2022).…”
Section: ) Social Communication Rolementioning
confidence: 99%